2012
DOI: 10.1161/circulationaha.111.082727
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Versus Clopidogrel in Patients With Acute Coronary Syndromes and a History of Stroke or Transient Ischemic Attack

Abstract: for the PLATO Study GroupBackground-Patients with acute coronary syndromes and history of stroke or transient ischemic attack (TIA) have an increased rate of recurrent cardiac events and intracranial hemorrhages. Methods and Results-We evaluated treatment effects of ticagrelor versus clopidogrel in patients with acute coronary syndrome with and without a history of prior stroke or TIA in the PLATelet inhibition and patient Outcomes (PLATO) trial. Of the 18 624 randomized patients, 1152 (6.2%) had a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 18 publications
7
46
0
6
Order By: Relevance
“…Similarly, Fuchs et al showed that the rate of peri-procedural stroke in an unselected group of patients undergoing PCI was 0.38% [14]. Although some studies suggest that a prior stroke in patients undergoing PCI is associated with more risks, such as cerebral hemorrhage, reinfarction and prolonged hospital stay [15,16], our study suggests that PCI is feasible and probably safe, if adequate standardized treatment were given before PCI, even for patients with a prior stroke. On the other hand, in our study, patients with prior recent stroke (ischemic stroke within 3 months) and hemorrhagic stroke were excluded from enrollment, which might have some e ects on the clinical outcomes in patients undergoing PCI suggesting an inherent selection bias.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, Fuchs et al showed that the rate of peri-procedural stroke in an unselected group of patients undergoing PCI was 0.38% [14]. Although some studies suggest that a prior stroke in patients undergoing PCI is associated with more risks, such as cerebral hemorrhage, reinfarction and prolonged hospital stay [15,16], our study suggests that PCI is feasible and probably safe, if adequate standardized treatment were given before PCI, even for patients with a prior stroke. On the other hand, in our study, patients with prior recent stroke (ischemic stroke within 3 months) and hemorrhagic stroke were excluded from enrollment, which might have some e ects on the clinical outcomes in patients undergoing PCI suggesting an inherent selection bias.…”
Section: Discussionsupporting
confidence: 52%
“…28 No increased risk of overall or intracranial bleeding existed with ticagrelor therapy in those with a history of stroke or TIA. 30 Subsequent analysis of the trial, spurred by the finding of no benefit in the North American cohort of patients, revealed that the benefits of ticagrelor over clopidogrel for reduction in ischaemic events are observed only when the daily aspirin dose is ≤100 mg, 31 which is now reflected in a recommendation on package labelling. 32…”
Section: Ticagrelormentioning
confidence: 99%
“…20 However, bleeding intracranially was not found to be related to a history of stroke or TIA (interaction P = .38); of the 1152 patients in PLATO with a history of stroke or TIA, only 4 patients receiving ticagrelor and 4 patients receiving clopidogrel had intracranial bleeding. 27 It is worth noting that ticagrelor is currently being evaluated as a monotherapy in a trial of "all-comers (unselected)" patients undergoing PCI (NCT01813435), with results expected in 2016.…”
Section: Plato Triton-timi 38mentioning
confidence: 99%
“…(Continuation of a P2Y 12 receptor inhibitor such as clopidogrel for longer than 12 months may be possible for patients receiving a drug-eluting stent [COR: IIb; LOE: C]. 6,27 ) Cardiac enzymes are initially negative but reveal a slight elevation on the second test (creatine phosphokinase, 500 µg/L; creatine kinase-MB fraction, 5.2 µg/L; troponin I, 1.03 µg/L), and the 12-lead electrocardiogram shows no ischemic changes. NSTE-ACS (NSTEMI) is diagnosed, and the patient is given a loading dose of clopidogrel (300 mg) in the emergency department and admitted to cardiac telemetry.…”
Section: Case Study 1: Nste-acsmentioning
confidence: 99%
See 1 more Smart Citation